IDENTIFIKASI SENYAWA TURUNAN HASIL FRAKSINASI KAYU AKAR ARTOCARPUS ODORATISSIMUS - Putri Ayu Mutmainnah; Aliefman Hakim; Lalu Rudyat Telly Savalas (Postgraduate, University of Mataram, 2017)
This research has made for identification derivate compound of fractionation derivate compound of fractionation root bark Artocarpus ododratissimus. Root bark A. dodoratissimus has macerated by methanol. Fractionation by using Vacuum Liquid Choromatography with eluen variation from nonpolar till polar (n-hexane 100%; n-hexane:ethyl acetate 9:1 till 1:9; ethyl acetate 100% and ethyl acetate:methanol 9,5:0,5 and 9:1) produce main fraction. Purified by used with Gravitation Coulumb Chomatograph produce seven main fraction. Identification based on FT-IR and 1H-NMR showed that the pure compound assumed phenyl prophane derivation.Keyword: Artocarpus odoratissimus, phenyl prophane